The effect of electroconvulsive therapy on hematologic inflammatory markers in schizophrenia in association with type of antipsychotic medication - Önen, Sinay; Taymur, İbrahim (The European Research Journal, 2020)
Objectives: In recent years there has been an increased interest on the role of inflammation in the pathophysiology of schizophrenia and a search for readily applicable prognostic markers. The impact of electroconvulsive therapy (ECT) on inflammatory function in schizophrenia is still unclear. The aim of this retrospective study is to compare pre- and post-ECT values of red cell distribution width (RDW), mean platelet volume (MPV), mean cell hemoglobin (MCH), mean cell hemoglobin concentration (MCHC), neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) which are considered to be inflammatory markers, and to discuss the findings in context of neuroinflammatory ethiology of schizophrenia. Methods: Inpatient files were reviewed via complete blood count (CBC), sociodemographic and clinical characteristics (e.g. gender, age, Body Mass Index (BMI), type of psychotropic medication). A total of 58 schizophrenic patients who underwent ECT were were compared in terms of pre- and post-ECT values of RDW, MPV, MCH, MCHC, NLR and PLR in association with type of psychotropic medication. Results: It was found that MPV, RDW, MCH and MCHC levels significantly decreased after ECT (p < 0.05), but no significant difference was found in terms of NLR and PLR (p > 0.05). When compared according to the type of psychotropic medication during ECT, MPV and MCHC were decreased after ECT in both typicaland atypical antipsychoticintervention groups (p < 0.05). ECT-related inflammatory marker changes were more likely to be associated with atypical antipsychotic medication use during ECT. Conclusions: Our results indicate that recurrent ECT sessions caused a change in the function of the immune system which might be considered to explain the therapeutic effects of ECT in schizophrenia.